PERANAN KOMISI INFORMASI DALAM MENSOSIALISASIKAN PERATURAN KOMISI INFORMASI UNTUK KETERBUKAAN INFORMASI PUBLIK DI PROVINSI BALI: - - Dewa Nyoman Suardana; Ni Made Yuliani; I Made Dian Saputra (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
This openness of information must be guarded simultaneously by the public and public bodies, openness of information can bring prosperity to the community, and become a tool towards accelerating development. If this information disclosure is implemented, the public will know many things, human resources will increase which will then become an asset for the government to support the acceleration of the realization of government programs. During the 13 (thirteen) years of promulgation, the public and public bodies have not followed up on it massively. Researchers are interested in researching "The Role of the Information Commission in Promoting Information Commission Regulations for Public Information Disclosure in Bali Province". The research uses a normative legal approach, namely in the form of library research. The research findings are: 1) The Information Commission's strategy in disseminating Information Commission Regulations for information disclosure for public bodies, namely: Use of public communication media, electronic and non-electronic channels; Advocacy, outreach and education to public bodies; Collaboration and synergy of program activities with public bodies; Involvement of public bodies in monitoring and evaluating public information disclosure and Central IC work programs. 2) Obstacles faced in disseminating Information Commission Regulations for information disclosure for public bodies include: Organizational structure support; Governance strengthening budget; Facilitate the improvement of the competence of commissioners and secretariat; Facilities and infrastructure; Obstacles to the implementation of public information services in public bodies. 3) Implications in disseminating information commission regulations for public bodies. Keywords: The Role of the Information, Commission, and Public Information Disclosure